The Influence of Work Attitude and Work Environment on the Performance of Educational Staff Through Job Satisfaction At Catholic University of Saint Thomas North Sumatera - Theresa Sisilia Situmorang; Prihatin Lumbanraja; Beby Karina Fawzeea Sembiring (PT FORMOSA CENDEKIA GLOBAL, 2025)
This research aims to determine and analyze the influence of work attitude and work environment on performance through job satisfaction. This research is associative and the type of data used is quantitative data. The population in this study consists of permanent educational staff at Universitas Katolik Santo Thomas. The number of samples in this study is 91 educational staff. The sampling technique used is saturated sampling. The data analysis used is Structural Equation Modeling. The results of this study indicate that work attitude and work environment have a direct, positive, and significant impact on job satisfaction and performance of the educational staff at Universitas Katolik Santo Thomas.